Dendritic silver self-assembly in molten-carbonate membranes for efficient carbon dioxide capture. Issue 6 (29th April 2020) - McNeil, Liam A.; Mutch, Greg A.; Iacoviello, Francesco; Bailey, Josh J.; Triantafyllou, Georgios; Neagu, Dragos; Miller, Thomas S.; Papaioannou, Evangelos I.; Hu, Wenting; Brett, Dan J. L.; Shearing, Paul R.; Metcalfe, Ian S.
Abstract : Self-assembling Ag dendritic networks provide ultrahigh CO2 permeability, whilst reducing membrane-volume-normalised Ag demand by an order of magnitude. Abstract : Membranes for CO2 capture should offer high permeant fluxes to keep membrane surface area small and material requirements low. Ag-supported, dual-phase, molten-carbonate membranes routinely demonstrate the highest CO2 fluxes in this class of membrane. However, using Ag as a support incurs high cost. Here, the non-equilibrium conditions of permeation were exploited to stimulate the self-assembly of a percolating, dendritic network of Ag from the molten carbonate. Multiple membrane support geometries and Ag incorporation methods were employed, demonstrating the generality of the approach, while X-ray micro-computed tomography confirmed that CO2 and O2 permeation stimulated self-assembly. We report the highest flux of Ag-supported molten-salt membranes to date (1.25 ml min −1 cm −2 at 650 °C) and ultrahigh permeability (9.4 × 10 −11 mol m −1 s −1 Pa −1 ), surpassing the permeability requirement for economically-competitive post-combustion CO2 capture, all whilst reducing the membrane-volume-normalised demand for Ag by one order of magnitude.